The first complete chloroplast genome of Thalictrum fargesii: insights into phylogeny and species identification - Chen, Shixi; Safiul Azam, Fardous Mohammad; Akter, Mst. Lovely; Ao, Li; Zou, Yuanchao; Qian, Ye (Frontiers in Plant Science, 2024)
Introduction Thalictrum fargesii is a medicinal plant belonging to the genus Thalictrum of the Ranunculaceae family and has been used in herbal medicine in the Himalayan regions of China and India. This species is taxonomically challenging because of its morphological similarities to other species within the genus. Thus, herbal drugs from this species are frequently adulterated, substituted, or mixed with other species, thereby endangering consumer safety. Methods The present study aimed to sequence and assemble the entire chloroplast (cp) genome of T. fargesii using the Illumina HiSeq 2500 platform to better understand the genomic architecture, gene composition, and phylogenetic relationships within the Thalictrum. Results and discussion The cp genome was 155,929 bp long and contained large single-copy (85,395 bp) and small single-copy (17,576 bp) regions that were segregated by a pair of inverted repeat regions (26,479 bp) to form a quadripartite structure. The cp genome contains 133 genes, including 88 protein-coding genes (PCGs), 37 tRNA genes, and 8 rRNA genes. Additionally, this genome contains 64 codons that encode 20 amino acids, the most preferred of which are alanine and leucine. We identified 68 SSRs, 27 long repeats, and 242 high-confidence C-to-U RNA-editing sites in the cp genome. Moreover, we discovered seven divergent hotspot regions in the cp genome of T. fargesii, among which ndhD-psaC and rpl16-rps3 may be useful for developing molecular markers for identifying ethnodrug species and their contaminants. A comparative study with eight other species in the genus revealed that pafI and rps19 had highly variable sites in the cp genome of T. fargesii. Additionally, two special features, (i) the shortest length of the ycf1 gene at the IRA-SSC boundary and (ii) the distance between the rps19 fragment and trnH at the IRA-LSC junction, distinguish the cp genome of T. fargesii from those of other species within the genus. Furthermore, phylogenetic analysis revealed that T. fargesii was closely related to T. tenue and T. petaloidium. Conclusion Considering all these lines of evidence, our findings offer crucial molecular and evolutionary information that could play a significant role in further species identification, evolution, and phylogenetic studies on T. fargesii.